Efektivitas Ekstrak Kulit Jeruk Berastagi (Citrus Sinensis L.) Yang Diberikan Secara Topikal terhadap Kadar Serum C-reactive Protein pada Luka Sayat Tikus Jantan (Rattus Norvegicus) - Siregar, Yohana Putri Jelita; Natali, Oliviti; Lubis, Adhayani; Sumantri , Dinda Triana; Perangin-Angin, Eka Lestari Br (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Cutaneous wounds in male rats (Rattus norvegicus) are widely used as models for wound-healing research. C-reactive protein (CRP) is an inflammatory biomarker that increases in response to injury. Berastagi orange peel extract (Citrus sinensis L.) is known for its anti-inflammatory properties; however, its effectiveness in reducing serum CRP levels in cutaneous wounds has not been extensively studied. Objective: This study aimed to evaluate the effectiveness of topically administered Berastagi orange peel extract on serum CRP levels in male rats with cutaneous wounds. Methods: A total of 25 male rats were divided into three groups: control, treatment with orange peel extract, and treatment with a standard ointment. Wounds were inflicted on the rats' backs, and treatments were administered for a few days. Serum CRP levels were measured using the ELISA method. Results: Results indicated that the group receiving Berastagi orange peel extract exhibited a significant reduction in CRP levels compared to the control group (p < 0.05). The standard ointment group also showed a reduction, but not as effectively as the orange peel extract. Conclusion: Berastagi orange peel extract significantly reduces serum C-reactive protein levels in male rats with cutaneous wounds. These findings support the use of natural extracts as alternatives in wound healing therapy.